Comparison of recovery characteristics with two different washout techniques of desflurane anaesthesia: A randomised controlled trial - R Sripriya; Charulatha Ravindran; Ravishankar Murugesan (Indian Journal of Anaesthesia, 2020)
Background: Rapid emergence with low soluble inhalational agents (IA) is offset by a significant association with emergence agitation (EA). Research on the influence of elimination methods of IA on recovery characteristics is very few. We conducted this study to compare the recovery characteristics of slow elimination (SE) of desflurane with purging technique. Methodology: Forty-five participants, 18–60 years, undergoing elective laparoscopic surgeries were randomised either into Group-P (n = 23) or Group-SE (n = 22). A standardised induction-maintenance protocol including desflurane and fresh gas flow (FGF) of 0.8 l/min was followed. During recovery, the FGF was increased in Group-P to 10 L/min and in Group-SE it was continued at 0.8 L/min. The decrement in end-tidal concentration of desflurane, time for emergence and extubation, EA and time for psychomotor recovery were noted. Results: Time for emergence (Group-SE: 22.8 ± 9 vs. Group-P: 5.6 ± 1.5 min; P = 0.000) and emergence to extubation duration (Group-SE: 128 ± 36 s vs. Group-P: 11.5 ± 1.7 s; P = 0.000) were longer in the Group-SE than in Group-P. EA occurred in 22.7% patients in Group-SE and in 4.3% patients in Group-P (P = 0.07). Psychomotor recovery to baseline values was seen in more number of patients in Group-SE than Group-P at 30 min. There was no difference between the groups at 60 min post-extubation. Conclusions: Slow elimination using FGF of 0.8 L/min significantly prolongs emergence even with low soluble agent like desflurane. SE is not beneficial in decreasing the incidence of EA or hastening psychomotor recovery. Purging technique is, therefore, a better-suited technique with fewer complications for eliminating desflurane.